2010
DOI: 10.1177/1534735409357758
|View full text |Cite
|
Sign up to set email alerts
|

Relative Biological Effectiveness and Cell-Killing Efficacy of Continuous Low-Dose-Rate 125I Seeds on Prostate Carcinoma Cells In Vitro

Abstract: The aim of this study was to determine the effects of 125 I seeds on prostate carcinoma (PC3) cells. The relative biological effectiveness of 125 I seeds on PC3 cells with respect to 60 Co g rays was 1.4. Both 4 Gy of 60 Co g ray and 125 I seed irradiation increased the percentage of cells in G 2 phase, but there was no significant difference between these 2 types of radiation. Significantly, 125 I seeds induced higher apoptotic rates of PC3 cells compared with 60 Co g ray irradiation. Furthermore, Bcl-2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
4
11
1
Order By: Relevance
“…Compared with SDR and FDR, CLDR caused severe total cell number decrease, due to enhanced cell death. The reported RBE of 125 I seed continuous low dose rate irradiation of different models and cell lines were among 1.2 and 2.1, and most of which were ranged from 1.3 to 1.5 [11,12,19-21]. Lehnert et al showed that 125 I irradiation caused increased RIF-1 cell death, and the RBE for 125 I compared with 60 Co gamma rays was 1.5 [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with SDR and FDR, CLDR caused severe total cell number decrease, due to enhanced cell death. The reported RBE of 125 I seed continuous low dose rate irradiation of different models and cell lines were among 1.2 and 2.1, and most of which were ranged from 1.3 to 1.5 [11,12,19-21]. Lehnert et al showed that 125 I irradiation caused increased RIF-1 cell death, and the RBE for 125 I compared with 60 Co gamma rays was 1.5 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that cell apoptosis of PANC-1 cell line increased after CLDR, with RBE for 125 I compared with 60 Co gamma rays being 1.39 [11]. Liao et al demonstrated that CLDR resulted in increased PC-3 cell apoptosis, with RBE for 125 I compared with 60 Co gamma rays being 1.41 [12]. In the present study, we have shown that the RBE for 125 I compared with 6 MV X- rays was 1.42, which is consistent with the previous data reported by our colleagues and others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its high precision and low complication rate, radioactive 125 I seed implantation has been widely applied in treatment of cancers, such as recurrent colorectal cancer [6,7], head and neck carcinoma and NPC [4,5]. Several studies have demonstrated that 125 I seed irradiation is more effective in inducing cell apoptosis in PANC-1 pancreatic [8] and CL187 colonic cells [9,10]. …”
Section: Introductionmentioning
confidence: 99%